Policy Evaluation Of Single Tuition Fee (Uang Kuliah Tunggal) Towards Educational Justice (Case Study on Rector Decision Letter of Brawijaya University Number 276/SK/2013 and 324/2014) - Setya Nugraha (Jurnal Administrasi Publik, 2015)
Abstract: Policy Evaluation Of Single Tuition Fee (Uang Kuliah Tunggal) Towards Educational Justice (Case Study On Rector Decision Letter Of Brawijaya University Number 276/SK/2013 And 324/2014) Single Tuition Fee (UKT) Policy in UB experienced by pros and cons. Students make demonstration which want to educational justice. Bureucrats make hearing forum to know what the problem to implementation UKT policy in UB. Two years since UKT implemented in UB there are many shortcomings that need to be evaluated. The aims of the single tuition fee policy should be democratic and justice. Single tuition fee policy evaluation is divided into three parts, namely input, process and output policies. Evaluation inputs used to discuss the source of law and understanding of the nominal calculation UKT reference to be used in the make of decision letter. Evaluation Process produces a nominal formulation UKT at the faculty level and resulted in the discovery UKT nominal calculation that does not refer to the existing regulations. Evaluation output is explained about the legal issues resulting product. Model of deliberative policy suitable in the roles of actors in the policy UKT. Nominal calculations, the source of law, and the product of law must be in accordance with the rules of law on it. Keywords: policy evaluation, single tuition fee, educational justice Abstrak: Evaluasi Kebijakan Uang Kuliah Tunggal Menuju Pendidikan Berkeadilan (Studi kasus Surat Keputusan Rektor Universitas Brawijaya Nomer 276/SK/2013 dan 324/2014). Kebijakan Uang Kuliah Tunggal (UKT) di UB terjadi pro dan kontra. Mahasiswa melakukan demonstrasi dengan menginginkan untuk pendidikan berkeadilan. Birokrat membuat forum dengar pendapat untuk mengetahui apa masalah yang terjadi dalam pelaksanaan kebijakan UKT di UB. Dua tahun sejak UKT diterapkan di UB ada banyak kekurangan yang perlu dievaluasi. Tujuan dari kebijakan uang kuliah tunggal harus demokratis dan berkeadilan. Evaluasi kebijakan uang kuliah tunggal dibagi menjadi tiga bagian, yaitu input, proses dan output. Evaluasi input membahas mengenai sumber hukum dan pemahaman tentang referensi perhitungan nominal UKT yang akan digunakan dalam membuat surat keputusan rektor. Evaluasi proses menghasilkan formulasi nominal UKT di tingkat fakultas dan menghasilkan perhitungan nominal UKT yang tidak mengacu pada peraturan yang ada. Evaluasi output dijelaskan tentang masalah yang dihasilkan oleh produk hukum. Model kebijakan deliberatif cocok digunakan dalam kebijakan UKT. Perhitungan nominal, sumber hukum, dan produk hukum harus sesuai dengan aturan hukum di atasnya. Kata kunci : evaluasi kebijakan, uang kuliah tunggal, pendidikan berkeadilan